2015
DOI: 10.1016/j.rbre.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and adiponectin in patients with systemic lupus erythematosus: clinical and laboratory correlations

Abstract: r e v b r a s r e u m a t o l . 2 0 1 5;5 5(2):140-145 w w w . r e u m a t o l o g i a . c o m . b r Leptin Adiponectin a b s t r a c t Objective: To evaluate the serum levels of leptin and adiponectin in patients with systemic lupus erythematosus (SLE) and correlate their levels with disease activity, presence of autoantibodies and clinical manifestations.Methods: 52 women with SLE and 33 healthy women were evaluated. The patients were divided into two groups, the first with active SLE and the second with ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
(51 reference statements)
0
8
0
4
Order By: Relevance
“…It has already been confirmed that serum levels of leptin increased significantly in patients with SLE, a finding that has been replicated in many studies from diverse countries, revealing that leptin can be considered as a novel biomarker in predicting the risk of SLE (80)(81)(82)(83). Recently, several possible mechanisms by which leptin modulates the development of SLE have been emphasized.…”
Section: Relationship Between Leptin and Systemic Lupus Erythematosusmentioning
confidence: 77%
See 1 more Smart Citation
“…It has already been confirmed that serum levels of leptin increased significantly in patients with SLE, a finding that has been replicated in many studies from diverse countries, revealing that leptin can be considered as a novel biomarker in predicting the risk of SLE (80)(81)(82)(83). Recently, several possible mechanisms by which leptin modulates the development of SLE have been emphasized.…”
Section: Relationship Between Leptin and Systemic Lupus Erythematosusmentioning
confidence: 77%
“…Nevertheless, the interaction between leptin and other inflammatory cells under SLE condition is not fully understood (87). Additionally, no significant difference was observed between patients with active and those with inactive SLE (80,88,89). Nevertheless, a lower leptin concentration was found with joint inflammation and neurological symptoms during a course of SLE (90).…”
Section: Relationship Between Leptin and Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Many studies showed that adiponectin was high in RA patients (17,18) and others (19,20) showed that adiponectin was high in SLE than control. On the other hand, Barbosa et al (21) , concluded that the level of adiponectin was not high in SLE patients. Another study reported that the mean adiponectin level was significantly lower in SLE patients compared to control (22) .…”
Section: Discussionmentioning
confidence: 96%
“…Однако у больных СКВ убедительных доказательств наличия связи между уровнем лептина и активностью или клиническими проявлениями заболевания до настоящего времени не получено [3, 4], а имеющиеся данные противоречивы. Так, в одной из работ выявлена ассоциация между большей концентрацией лептина и поражением почек [15], тогда как в другой зависимости протеинурии от АЦК не обнаружено [16]. D. Chougule и соавт.…”
Section: Introductionunclassified
“…[18], наоборот, выявили более низкий уровень лептина при поражении суставов и центральной нервной системы. Отсутствие связи между концентрацией лептина и активностью СКВ продемонстрировано в нескольких исследовани-ях [5,15,[19][20][21], наряду с этим М. Vadacca и соавт. [22] сообщили о прямой, а D. Chougule и соавт.…”
Section: Introductionunclassified